THE EFFECT OF WORKLOAD, JOB SATISFACTION, WORK-LIFE BALANCE, AND SOCIAL SUPPORT ON EMOTIONAL EXHAUSTION IN EMPLOYEES - Cahyaningrum, Regita Dwi; Kasmawati, Yuni (Universitas Indo Global Mandiri Palembang, 2025)
This study aims to examine the influence of workload, job satisfaction, work-life balance, and social support on emotional exhaustion among employees of public accounting firms. The research method used is quantitative descriptive. The data analysis technique employed in this study is multiple linear regression. The sampling method used in this research is saturation sampling, with a total sample size of 93 employees. Data were collected through a questionnaire using a Likert scale, which was processed using Microsoft Excel 2019 and SmartPLS version 4.1.0.9. The results of this study indicate that the variables of workload and worklife balance have a positive and significant effect on emotional exhaustion. Meanwhile, the variables of job satisfaction and social support have a negative and insignificant effect on emotional exhaustion. These findings are expected to help reduce the level of emotional exhaustion among employees of public accounting firms.